AN ANALYSIS OF COMPENSATION AND COMPETENCE EFFECTS TOWARDS LECTURER PERFORMANCE AT STMIK ROYAL KISARAN - Pristiyanilicia Putri; Havid Syafwan; Febri Dristyan (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2020)
The purpose of this research is to analyze the effect of compensation and competence partially andsimultaneously on the lecturer’s performance of STMIK Royal Kisaran in Asahan Regency, NorthSumatera. The population of this research was all regular (permanent) lecturers at STMIK Royaltotally of 90 people where data collection was carried out by distributing questionnaires and interviewsto those permanent lecturers. The quantitative method was used in this study, while the analyticalmethod used was multiple regression analysis by performing the F test and t test where the data isprocessed using SPSS software. From the results of multiple regression analysis the equation Y = 8.032+ 0.181X1 + 0.339X2 is obtained. Partially and simultaneously the compensation and competencevariables affect the performance variables of lecturers at STMIK Royal Kisaran.